2002
DOI: 10.1111/1058-7195.00009
|View full text |Cite
|
Sign up to set email alerts
|

Farm-Level Modeling for Bigger Issues

Abstract: The purpose of this paper is to discuss how farm-level modelers can best extend their research to address issues broader than just farm income. The paper describes how tradeoff curves are a valuable tool for summarizing the missing information to policy makers on economic problems related to sustainability issues and agriculture. We outline steps an economic researcher could follow in developing an integrated farm-level model that successfully links changes in environmental quality with agricultural practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 15 publications
(6 reference statements)
0
35
0
Order By: Relevance
“…The first category contains the optimisationoriented approaches. As with Simon's theory (1969), design is mainly seen as a problem-solving process (Weersink et al 2002). Emphasis is placed on the computational exploration of the solution space by a problem-solving algorithm.…”
Section: Preamblementioning
confidence: 99%
See 1 more Smart Citation
“…The first category contains the optimisationoriented approaches. As with Simon's theory (1969), design is mainly seen as a problem-solving process (Weersink et al 2002). Emphasis is placed on the computational exploration of the solution space by a problem-solving algorithm.…”
Section: Preamblementioning
confidence: 99%
“…Whereas the outputs (in the form of knowledge embodied in peer-reviewed articles, software or datasets) of a design project are easily traceable, the outcomes (changes in values, attitudes and behaviour in the world beyond the walls of the research institute; Matthews et al 2011) are seldom analysed (Pacini et al 2004a, b), partly because of the limited literature for their formal evaluation (Weersink et al 2002). Yet design is an applied activity and the support of social scientists is required to evaluate, and if necessary improve, the extent to which farming system design processes affect the intended users of their products, and whether or not these products are made use of.…”
Section: Research Agendamentioning
confidence: 99%
“…Agro-environmental indicators can be calculated, simulated with models or directly measured with different levels of detail, proportionally to the aims of the evaluation exercise. Given the above-mentioned layout of the system based on ecological concepts, the procedural steps to apply the framework are reported in Figure 2, so as they were modified from Weersink et al (2002), and explained in the following sections.…”
Section: Aesis General Structurementioning
confidence: 99%
“…Some focus on environmental impact (see, for an example, the critical review of 12 indicatorbased methods reported by Van der Werf and Petit, 2002), others hold a stronger holistic component and consider socio-economic aspects as well. Examples of frameworks of the latter type broadly applied in the agricultural sector are the International Framework for Evaluating Sustainable Land Management (FESLM, Smith and Dumanski, 1994), the framework of the Research Network on Integrated and Ecological Arable Farming Systems for EU and Associated Countries (Vereijken, 1999), the Checklist for Sustainable Landscape Management (Van Mansvelt and Van der Lubbe, 1999), the Problem-Solving Framework for Modelling Sustainability Issues (Weersink et al, 2002) and the Framework for Assessing the Sustainability of Natural Resource Management Systems (MES-MIS, López-Ridaura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation